Towards the decolonisation of disability: A systematic review of disability conceptualisations, practices and experiences of First Nations people of Australia. (July 2022) - Puszka, Stefanie; Walsh, Corinne; Markham, Francis; Barney, Jody; Yap, Mandy; Dreise, Tony
Abstract: In many settler-colonial countries, Indigenous people do not access disability services at rates commensurate with disability prevalence. Existing research suggests that services often do not reflect Indigenous values and social practices, impacting on accessibility. Furthermore, disability services have historically been implicated in processes of colonisation. There is an urgent need to decolonise disability services. Understanding Indigenous knowledge and experience of disability is a necessary step towards achieving this. We systematically reviewed the disability conceptualisations, practices and experiences of First Nations peoples of Australia. Twelve studies met inclusion criteria. There was a consensus among these studies that Western constructs of disability do not resonate with many First Nations people across Australia. The studies reported that many First Nations people conceptualise most disabilities as unremarkable conditions that reflect the normal range of human diversity, although some conditions may be associated with social stigma. Inclusive attitudes and practices of caregiving in First Nations families facilitate the participation of First Nations people with disabilities in family and community life. However, ableism and racism in broader society combine to exclude many First Nations peoples with disabilities from public spaces and from labour markets. Disability services regularly fail to reflect First Nations values and social practices, and can lead to further disempowerment and marginalisation due to diagnostic processes; displacement from country and communities; gendered discrimination; and poor relationships with service providers. We argue that intersectional experiences of colonialism, racism, ableism and sexism, particularly in disability services, can lead to the marginalisation of First Nations participants and families. The decolonisation of disability services requires services to embrace diverse First Nations values and practices associated with human capability, social participation and caregiving. Decolonising disability services also necessitates First Nations control of the governance of disability services and reform across service, organisational, systemic and conceptual levels. Highlights: This is the first systematic review of Indigenous views of disability and services. The WHO biopsychosocial model does not adequately reflect First Nations experience. Many First Nations people desire greater support for family caregiving. The intersection of racism, ableism and sexism impacts disability experience. A decolonisation agenda in disability services necessitates systemic change.